2006
DOI: 10.1007/bf02913092
|View full text |Cite
|
Sign up to set email alerts
|

Oxidised LDL, HDL cholesterol, LDL cholesterol levels in patients of coronary artery disease

Abstract: Coronary artery disease is a major cause of morbidity and has various risk factors. Lipid profile i.e. low HDL-cholesterol, high LDL cholesterol, high total cholesterol, high triglycerides playing important role in its causation. Recently interest has been shown in the oxidized fraction of LDL as one of the risk factors. In the present study 60 age and sex matched normal healthy individuals were taken as controls and 60 patients of CAD were taken. Cholesterol was measured by enzymatic method, HDL cholesterol b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
4
13
2
Order By: Relevance
“…This significant reduction in TG levels may be attributed to an increasing lipid peroxidation activity (LPL), which will lead to an increase in the degredation of TG and/or reduction in VLDL which is usually produced in the liver and aids in lipolytic removal of TG-rich lipoproteins from the circulation (Wang et al, 2003;Megalli et al, 2006). Studies have shown that elevated VLDL-C is associated with a high TG, since VLDL-C carries the highest amount of TG in the body (Ghosh et al, 2006) as observed in this study.…”
Section: Discussionsupporting
confidence: 80%
“…This significant reduction in TG levels may be attributed to an increasing lipid peroxidation activity (LPL), which will lead to an increase in the degredation of TG and/or reduction in VLDL which is usually produced in the liver and aids in lipolytic removal of TG-rich lipoproteins from the circulation (Wang et al, 2003;Megalli et al, 2006). Studies have shown that elevated VLDL-C is associated with a high TG, since VLDL-C carries the highest amount of TG in the body (Ghosh et al, 2006) as observed in this study.…”
Section: Discussionsupporting
confidence: 80%
“…[3][4][5][6][7][8][9][10] Lowering of high-density lipoprotein (HDL)-cholesterol (HDL-C) is a common phenomenon observed in myocardial infarction (MI) patients. [3][4][5][6][7][8][9][10] Elevated Low density lipoprotein (LDL)-cholesterol (LDL-C) is considered the most important risk factor for CAD and its oxidation plays a central role in atherogenesis. Subendothelial accumulation of foam cells initiates the process of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey reveals dyslipidaemic subjects are more prone to myocardial infarction, due to increased free radical generation and ischemia as it is a conventional risk factor. (Malhotra et al, 2003;Mishra et al, 2005;Ghosh et al, 2006;Patil et al, 2007;Rajasekhar et al, 2004;Rani et al, 2005;Gomez et al,1996). Lowering of high density lipoprotein-cholesterol (HDL-C) is a common phenomenon observed in MI patients supported by previous studies (Malhotra et al, 2003;Mishra et al, 2005;Ghosh et al, 2006;Patil et al, 2007;Rajasekhar et al, 2004;Rani et al, 2005).…”
mentioning
confidence: 99%
“…(Malhotra et al, 2003;Mishra et al, 2005;Ghosh et al, 2006;Patil et al, 2007;Rajasekhar et al, 2004;Rani et al, 2005;Gomez et al,1996). Lowering of high density lipoprotein-cholesterol (HDL-C) is a common phenomenon observed in MI patients supported by previous studies (Malhotra et al, 2003;Mishra et al, 2005;Ghosh et al, 2006;Patil et al, 2007;Rajasekhar et al, 2004;Rani et al, 2005). High density lipoprotein-cholesterol (HDL-c) is the most important independent protective factor for arteriosclerosis which underlies coronary heart disease (CHD).…”
mentioning
confidence: 99%